MANFAAT PELESTARIAN WARISAN BUDAYA “HIDUP” DI SEWO, SOPPENG - Danang Wahju Utomo (Balai Arkeologi Provinsi Sulawesi Selatan, 2001)
Soppeng rich with megalithic tradition remains, probably similar with Toraja. Unfortunately, archaeological interests and development sectors are not design within multi-sectors planning blueprint. Archaeological remains and ceremonial activities, for instance Sewo site, is lack with appropriate management which can be sell to support Soppeng's local income increase of tourism sector. In fact, an integrated Sewo site exploitation and management may brings a new concept which has its implication widely, even with social and economical measurements as well.